2012
DOI: 10.1074/jbc.m111.317214
|View full text |Cite
|
Sign up to set email alerts
|

The FKBP38 Catalytic Domain Binds to Bcl-2 via a Charge-sensitive Loop

Abstract: Background: FKBP38 regulates the prosurvival activity of Bcl-2 in apoptosis signaling. Results: The catalytic domain of FKBP38 interacts with helix 4 in Bcl-2. Conclusion: An electrostatic interaction modulates transient complex formation between FKBP38 and Bcl-2. Significance: The protein complex provides a molecular basis for FKBP38-mediated Bcl-2 regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Interestingly, FKBP38 peptidylprolyl isomerase activity critically depends on complex formation with Ca 2 + /calmodulin [68]. It has been proposed that only the 'active' Ca 2 + /calmodulin-FKBP38 complex can bind Bcl-2 [68], which is consistent with findings that a charge-sensitive loop within the catalytic domain of FKBP38 is responsible for Bcl-2 binding [69]. This provides an interesting link between Ca 2 + signalling and Bcl-2-protein function.…”
Section: Bcl-2 Proteins As Targets Of Immunophilinssupporting
confidence: 53%
“…Interestingly, FKBP38 peptidylprolyl isomerase activity critically depends on complex formation with Ca 2 + /calmodulin [68]. It has been proposed that only the 'active' Ca 2 + /calmodulin-FKBP38 complex can bind Bcl-2 [68], which is consistent with findings that a charge-sensitive loop within the catalytic domain of FKBP38 is responsible for Bcl-2 binding [69]. This provides an interesting link between Ca 2 + signalling and Bcl-2-protein function.…”
Section: Bcl-2 Proteins As Targets Of Immunophilinssupporting
confidence: 53%
“…FKBP38 mediates neuronal apoptosis ( Maestre-Martinez et al, 2011 ), and FKBP38 −/− mice die soon after birth ( Shirane et al, 2008 ). Th e catalytic domain of FKBP38 binds to Bcl-2 through a charge-sensitive loop ( Haupt et al, 2012 ) to control apoptosis; this interaction is regulated by Ca 2+ and Rheb ( Ma et al, 2010 ; Maestre-Martinez et al, 2011 ; Haupt et al, 2012 ). FKBP38 is associated with many functions, from programmed cell death to the development of the embryo and postnatal brain.…”
Section: Introductionmentioning
confidence: 99%
“…Recent confocal microscopy results have showed that FKBP8 and NS5A protein of the classical swine fever virus colocalize in the cytoplasm, suggesting a strong interaction between the proteins . Furthermore, RNAi‐mediated silencing of FKBP8 gene can induce the activation of mTOR signaling in goat fetal fibroblasts via protein‐protein interaction through its ankyrin‐repeat domain . FKBP8 can interact with the antiapoptotic protein B‐cell lymphoma 2 (Bcl‐2) and protect it from degradation …”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, RNAi-mediated silencing of FKBP8 gene can induce the activation of mTOR signaling in goat fetal fibroblasts via protein-protein interaction through its ankyrin-repeat domain. [30][31][32][33] FKBP8 can interact with the antiapoptotic protein B-cell lymphoma 2 (Bcl-2) and protect it from degradation. 34 The spatial localization data between FKBP8 and RIG-I, VISA, and TBK1 indicate that FKBP8 translocates from the cytoplasm to the mitochondrial outer membrane and endoplasmic reticulum membrane to participate in the RLR-VISA signaling pathway and thus plays a crucial role in the antiviral process.…”
Section: Discussionmentioning
confidence: 99%